The spectrum and efficacy of antiepileptic drugs in patients with infantile spasms in Russia - T. G. Okhapkina; I. V. Shuljakova; E. S. Ilina; G. V. Kalmykova; M. V. Prytkina; E. D. Belousova (Эпилепсия и пароксизмальные состояния, 2018)
Recently, the International League Against Epilepsy (ILAE) defined epileptic spasms as a separate type of seizures. According to the international recommendations, the treatment of infantile  spasms (IS) begins with hormones or vigabatrin (in the cases of tuberous sclerosis complex –  TSC). However, in the Russian Federation, other antiepileptic drugs (AEDs) are often used as the first line medications.Aim: to analyze the current practice of prescribing AEDs for the treatment of epileptic spasms.Materials and Methods. We studied the medical records of 175 patients with IS (59 of them with TSC) hospitalized for the treatment with hormonal therapy.Results. Valproic acid was the most commonly prescribed antiepileptic drug in patients with IS  (more than in 80% of cases), both in children with TCS (49/59) and without TCS (102/116). As  expected, the clinical effect (cessation of IS and suppression of hypsarrhythmia) of valproic acid  was insufficient: it was observed in 9/49 (18.4%) children with TSC and in 12/102 (11.2%)  children without TSC. Although ethosuximide, oxcarbazepine, and carbamazepine were known to  be ineffective in IS, they were prescribed by medical doctors and taken by IS patients with no  clinical improvement at all. Taking into account the possible limitation of this analysis (not all of the children were consulted and hospitalized in our clinics), the real efficacy of AEDs might be some higher.Conclusion. We then conclude that the treatment of IS in the Russian Federation is not in line with the international recommendations and the worldwide clinical practice. There is an urgent need in  updating the national standards for the diagnosis and treatment of IS. The work in this direction is now under way in the Russian Federation.